I formati pedagogici nelle pratiche degli insegnanti - Pentucci, Maila (Ricerca-Formazione - Open Access, 2018)
This book wants to deepen the concept of pedagogical format, intended as an organized microstructure of the didactic action, present in the teachers' practices at a pre-reflective and pre-conscious level and incorporated in the action of the teacher and the students.